2022
DOI: 10.1155/2022/1011415
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effects of Primary Nursing on Diabetic Nephropathy Patients Undergoing Hemodialysis and Its Impact on the Inflammatory Responses

Abstract: Objective. To assess the clinical effects of primary nursing on diabetic nephropathy patients undergoing hemodialysis and its impact on inflammatory responses. Methods. Between July 2019 and April 2021, 80 patients with diabetic nephropathy who underwent hemodialysis in our institution were recruited and assigned at a ratio of 1 : 1 to receive either routine nursing (routine group) or primary nursing (primary group). The outcome measures included nursing outcomes, inflammatory factor levels, and psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%